Lyme neuroborreliosis as initial expression of Lyme disease in an elderly patient - Emidio Mata; Bárbara Lage Garcia; André Pereira; Joana Rego; Flávia Santos; Carlos Fernandes; Jorge Cotter (European Journal of Case Reports in Internal Medicine)
Background: Lyme disease (LD) is a multisystemic infection caused by Borrelia burgdorferi and transmitted by Ixodes ticks, affecting the skin, nervous system, heart and joints. Neuroborreliosis (LNB), a nervous system manifestation of LD, occurs in 10–15% of cases and may present with neurological symptoms at varying stages. Case description: We present the case of an 84-year-old man, admitted to the emergency department following a seizure, with fever and oropharyngeal erythema. After the administration of penicillin for presumed tonsillitis, a generalised skin rash developed and spontaneously resolved after 4 hours. Within 24 hours, two well-defined round erythematous lesions were observed on the neck and shoulder. Due to new onset of confusion and lethargy a lumbar puncture was performed, revealing polymorphonuclear pleocytosis, elevated protein levels and normal glucose. An empirical ceftriaxone course was started for suspected neuroborreliosis. Neuroborreliosis was diagnosed based on the clinical presentation of fever and neurological changes, with supporting cutaneous manifestations and compatible Borrelia burgdorferi serology. The initial rash was interpreted as a Jarisch–Herxheimer reaction, and the two skin lesions were classified as erythema migrans. After completing treatment, the patient made a full recovery. Conclusion: This case underscores the diagnostic complexity of LNB as an initial manifestation of LD, particularly in elderly patients. Early neurological symptoms, often preceding classic cutaneous signs, may lead to diagnostic delays. This highlights the importance of maintaining clinical suspicion for LD, given the limitations of serological and cerebrospinal fluid (CSF) testing. Prompt recognition and intervention are essential to prevent progression and ensure favourable outcomes.